2010
DOI: 10.1111/j.1539-6924.2010.01536.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Human Error Probability Assessment Using Fuzzy Modeling

Abstract: Human error is one of the significant factors contributing to accidents. Traditional human error probability (HEP) studies based on fuzzy number concepts are one of the contributions addressing such a problem. It is particularly useful under circumstances where the lack of data exists. However, the degree of the discriminability of such studies may be questioned when applied under circumstances where experts have adequate information and specific values can be determined in the abscissa of the membership funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Ferdous et al found that trapezoidal and triangular fuzzy numbers form a sound practical alternative to reflect uncertainties and fuzziness of human justifications. These two types of fuzzy numbers have a smooth transition from one linguistic value to another value …”
Section: Fuzzy Probability Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferdous et al found that trapezoidal and triangular fuzzy numbers form a sound practical alternative to reflect uncertainties and fuzziness of human justifications. These two types of fuzzy numbers have a smooth transition from one linguistic value to another value …”
Section: Fuzzy Probability Methodsmentioning
confidence: 99%
“…These two types of fuzzy numbers have a smooth transition from one linguistic value to another value. [25] Basic principle and definition of fuzzy probability are briefly introduced below. More details can be found in reference by Li.…”
Section: Basic Principlementioning
confidence: 99%
“…Since previous researchers confirm that trapezoidal and triangular fuzzy numbers form a sound practical alternative to reflect uncertainties, inaccuracy and fuzziness of human justifications involving in linguistic values (Wolkenhauer, 2001;Ferdous et al, 2011) and have smooth transitions from one linguistic term to another term (Ung and Shen, 2011). These types of membership functions are considered in this study to represent basic event failure possibilities.…”
Section: Fuzzificationmentioning
confidence: 99%
“…Finally, the center of gravity method is introduced to defuzzify the linguistic variables into crisp values, which is the action failure probability. The fuzzy logic model is also introduced in the other research papers for human reliability analysis …”
Section: Introductionmentioning
confidence: 99%